IMPLEMENTASI MODUL FISIKA MODERN BERBASIS KONSTRUKTIVISME - nova susanti (Universitas Batanghari Jambi, 2016)
Still limited learning resources available in the library and the inability of most college students to purchase learning resources either in the form of a book or module.Then the necessity created a learning resource in the form of learning materials in the form of modules. This research aims to look at the results of a study of college students in learning using a module-based constructivism. The research is the research action class (PTK) consisting of three cycles, each cycle consists of four stages, namely action planning, implementation, observation, evaluation and reflection. The subject of this study is a three-semester student physical education PGMIPAU. The object of this research is the result of student learning. From the results of the studyobtained the use of Constructivism-based modern physics module on cycle 1 median – median test results of students are 50.54, on average cycle 2 – align students ' test results was 61.00, and median – median 3 cycle test results of students are 66.00, so it can be concluded that the use of Constructivism-based modern physics modules can improve student learning outcomes.